THE ROLE OF SOCIAL MEDIA IN SHAPING ADOLESCENT IDENTITY: A SOCIAL-PSYCHOLOGICAL PERSPECTIVE - Nur Hasan; Ethan Tan; Ava Lee (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Adolescence represents a critical developmental stage during which individuals actively construct personal and social identities through interactions with their surrounding environments. Rapid growth in social media usage has transformed the contexts in which identity formation occurs, creating new opportunities for self-expression, social connection, identity exploration, and community participation. Digital platforms increasingly function as influential social spaces that shape adolescents’ perceptions of themselves and others. This study aims to examine the role of social media in shaping adolescent identity from a social-psychological perspective by exploring the relationships among social media engagement, identity exploration, online self-presentation, social validation, and self-concept development. A mixed-methods research design employing a sequential explanatory approach was utilized. Quantitative data were collected from 500 adolescents through validated measures of social media engagement, identity development, self-concept clarity, and psychological well-being. Qualitative interviews were conducted to explore participants’ experiences of identity construction within digital environments. Structural Equation Modeling and thematic analysis were employed to analyze the data. Findings revealed that social media engagement significantly influenced identity exploration, online self-presentation, perceived social validation, and self-concept clarity. Identity exploration emerged as a key mediating factor linking digital participation to identity development. The study concludes that social media serves as a powerful social-psychological context for adolescent identity formation, with developmental outcomes shaped by the quality of online interactions, patterns of engagement, and the nature of social feedback received within digital communities.